Left atrial dysfunction relates to symptom onset in patients affected by severe degenerative mitral regurgitation - Giacomo Ingallina; Gabriele Paci; Davide Margonato; Leonardo Italia; Francesco Ancona; Stefano Stella; Federico Biondi; Annamaria Tavernese; Martina Belli; Monica Barki; Michele Morosato; Jennifer Wong; et al. (Cardiovascular Ultrasound)
Abstract Background Left atrium (LA) is far from simply being a passive connection chamber between left ventricle and the pulmonary circulation. In patients affected by mitral regurgitation (MR) an impairment in LA compliance and reservoir function, which can be evaluated using Speckle Tracking echocardiography, lead to elevated atrial pressure, resulting in increased pulmonary capillary pressures and the onset of dyspnea. Our study aims to evaluate the correlation between left atrial dysfunction and symptoms onset in patients with severe degenerative MR. Identifying left atrial dysfunction as a predictor of symptoms could be helpful to guide management strategy of asymptomatic patients with severe degenerative MR. Methods In a retrospective analysis, we examined all patients diagnosed with severe degenerative MR who underwent evaluation for potential cardiac surgery using transthoracic and transesophageal echocardiogram between May 2019 and July 2022 at IRCCS San Raffaele Hospital. The cohort was stratified into two groups: symptomatic patients (NYHA > I) and asymptomatic (NYHA = I) patients. A comprehensive assessment of LA function and compliance was performed including: LA fractional atrial change, LA reservoir strain (LASr), LASr/E/e’, and LA reservoir work. Results The final study cohort comprised 401 patients. There were no significant differences observed in terms of left ventricle size, function, and mitral regurgitation volume between the two groups. Atrial dysfunction and dilatation were significantly associated with symptoms. Among the atrial functional indexes LASr, a marker of LA compliance, showed the strongest association with symptoms (AUC: 0.85, OR: 7.45, p < 0.001). A LASr value below 22% emerged as an effective threshold, identifying symptomatic patients with 86% specificity and 68% sensitivity. Conclusions The onset of symptoms in severe degenerative mitral regurgitation (MR) is closely associated with left atrial dysfunction. LASr < 22% identified symptomatic patients with 86% specificity and 68% sensitivity. Graphical Abstract